Robo-Advising on South African Exchange Traded Funds utilizing Prospect Theory - Jacobson, Ryan Jonathan (African Institute of Financial Markets and Risk Management, 2020)
Robo-advising is an emerging trend in markets around the world. The term has come to refer almost exclusively to automated advisory services for financial investments or wealth management. Currently, in the South African market, financial services firms offer their own robo-advising platforms that only provide automated advice about their own products. This paper investigates the possibility of a roboadvising platform existing outside of these financial institutions. The paper reviews the preconditions that make robo-advising possible. Namely, risk profiling, portfolio allocation, availability of ETFs and accessible online trading platforms. The research shows that independent robo-advisers are possible in South Africa and a minimum viable implementation is presented.